2021
DOI: 10.3389/fimmu.2020.603939
|View full text |Cite
|
Sign up to set email alerts
|

A20 Inhibits Intraocular Inflammation in Mice by Regulating the Function of CD4+T Cells and RPE Cells

Abstract: A20 is a negative regulator of inflammation and immunity and plays a role in several autoimmune and inflammatory diseases. Here, we demonstrate that A20 overexpression significantly ameliorates severity of EAU by inhibiting the infiltration of Th1 and Th17 cells, and by protecting integrity of the blood retinal barrier. In vitro studies showed that A20 silencing could promote CD4+T cells toward a Th1 and Th17 phenotype. A decreased expression of A20 in CD4+T cells was noticed in active BD patients but not in V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Then, EAU mice were fed a special LCA diet (0.01%) or normal diet. Clinical manifestations and histopathological changes in the mice were evaluated as previously described 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, EAU mice were fed a special LCA diet (0.01%) or normal diet. Clinical manifestations and histopathological changes in the mice were evaluated as previously described 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The PrimeScript RT reagent kit (Takara, Dalian, China) was used to synthesize cDNA from the RNA. The resultant DNA was amplified by real-time PCR as previously reported 1 . The sequences of the primers used in this study are shown in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A20-dependent downregulation of NF-κB-mediated inflammation is further underlined by the fact that NF-κB activity is negatively regulated by A20 overexpression in mice. In addition, patients with an active autoimmune phenotype due to Behcet’s disease reveal a decreased expression of A20 in CD4+ T cells [ 72 ].…”
Section: Ubiquitin and Ubiquitin-like Proteins In T-lymphocytesmentioning
confidence: 99%